Legal Protection for Child Victims of Sexual Violence at the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) of Jember Regency - Ghana Nabila Ersa; Sapti Prihatmini; Fanny Tanuwijaya; Dina Tsalist Wildana (Journal of Feminism and Gender Studies, 2026)
Conditions in Indonesia show that cases of violence, crime, and sexual harassment are increasing. Sexual violence not only occurs against adults but also against children. Children are vulnerable to becoming victims of sexual violence, this is because they are in a weaker position and cannot protect themselves. This study aims to determine the role and service mechanisms of the UPTD PPA Jember Regency in providing legal protection to child victims of sexual violence, and to determine the inhibiting and supporting factors of the UPTD PPA Jember Regency in implementing protection for child victims of sexual violence. The empirical legal research method uses two approaches, namely the Legal Approach and the Sociology of Law. The location of this research is the Regional Technical Implementation Unit for the Protection of Women and Children of Jember Regency, the research subjects are UPTD PPA companion officers, parents/guardians of victims, and child victims. Primary data sources were obtained through interviews, observation, and documentation, while secondary data are divided into two forms, namely primary legal materials and secondary legal materials. Data collection was carried out through data reduction, data presentation, and drawing and verifying conclusions. The researcher used descriptive analytical techniques for primary and secondary data.